Development of a Fully Coupled Biogeochemical Reactive Transport Model to Simulate Microbial Oxidation of Organic Carbon and Pyrite Under Nitrate‐Reducing Conditions. Issue 11 (23rd November 2018) - Knabe, Dustin; Kludt, Christoph; Jacques, Diederik; Lichtner, Peter; Engelhardt, Irina
Abstract: In regions with intensive agriculture nitrate is one of the most relevant contaminants in groundwater. Denitrification reduces elevated nitrate concentrations in many aquifers, yet the denitrification potential is limited by the concentration of available electron donors. The aim of this work was to study the denitrification potential and its limitation in natural sediments. A column experiment was conducted using sediments with elevated concentrations of organic carbon (total organic carbon 3, 247 mg C/kg) and pyrite (chromium reducible sulfur 150 mg/kg). Groundwater with high nitrate concentration (100 mg/L) was injected. Measurements were taken over 160 days at five different depths including N‐ and S‐isotope analysis for selected samples. A reactive transport model was developed, which couples nitrate reduction with the oxidation of organic carbon (heterotrophic denitrification) and pyrite (autolithotrophic denitrification), and considers also transport and growth of denitrifying microbes. The denitrification pathway showed a temporal sequence from initially heterotrophic to autolithotrophic. However, maximum rates were lower for heterotrophic (11 mmol N/(L*a)) than for autolithotrophic denitrification (48 mmol N/(L*a)). The modeling showed that denitrifying microbes initially preferred highly reactive organic carbon as the electron donor for denitrification but were also able to utilize pyrite. The results show that after 160 days nitrate increased again to 50 mg/L. At this time only 0.5% of the total organic carbon and 46% of the available pyrite was oxidized. This indicates that denitrification rates strongly decrease before the electron donors are depleted either by a low reactivity (total organic carbon) or a diminishing reactive surface possibly due to the presence of coatings (pyrite). Key Points: Temporal evolution from heterotrophic to autolithotrophic denitrification for constant boundary conditions due to microbes preferring organic carbon Denitrification rates can drop significantly prior to total depletion of electron donors Nitrite may precede nitrate downstream of a nitrate source due to electron donor competition